Isolated Population of Proboscis Monkeys and their Status in Sulaman Lake Forest Reserve, Sabah, Malaysia - Mohd. Aminur Faiz Suis; Marrynah Matami; Miyabi Nakabayashi; Aini Hasanah Abd Mutalib; Fazidah Ismail; Fadzilah Awang Kanak; Joseph Tangah (Tropical Life Sciences Research, 2025)
Proboscis monkeys are largely confined along the eastern coastal zone of Sabah, Malaysia. Sulaman Lake Forest Reserve (SLFR) is the only Class V Mangrove Forest Reserve in the forestry district of Kota Kinabalu, Sabah. This study is in accordance with the conservation strategies outlined in the Sabah Proboscis Monkey Action Plan (2019–2028), which is to focus on areas that have not been surveyed. Prior to this study, the status of proboscis monkeys in this reserve had not been scientifically documented. In addition, the habitat of this colobine species along the coastal zone of Sulaman Bay will be impacted by the construction of Pan Borneo Highway (Work Package 9). Hence, we intend to shed light on the status of proboscis monkeys in the SLFR including local threats to their population. This study discovered a small and isolated relict population of proboscis monkeys through a boat survey approach, which was also derived from interview sessions with local communities. We found that the degradation of mangrove forest integrity is a major threat to this population in the SLFR. It is hoped that this study will trigger more research, especially population size estimation, because such baseline information is crucial in the formulation of effective conservation programmes.